2016
DOI: 10.1002/stem.2412
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells are Recruited and Activated into Carcinoma-Associated Fibroblasts by Prostate Cancer Microenvironment-Derived TGF-β1

Abstract: Tumor stromal cells can supply appropriate signals that may develop aggressive phenotypes of carcinoma cells and establish a complex scenario which culminates in metastasis. Recent works proposed that bone marrow-derived mesenchymal stem cells (MSC) are recruited to primary tumors. However, the exact functions of these cells in the tumor microenvironment are not well characterized, as it is reported that MSC can either promote or inhibit tumor progression. In the present study, we aim at investigating the sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
146
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(152 citation statements)
references
References 59 publications
1
146
0
1
Order By: Relevance
“…We successfully simulated directional migration of MSCs toward human breast cancer cells and their conditioned medium in vitro. Our results complement the evidence that MSCs tend to migrate toward cancer cells, 13,18 cancer cell-conditioned medium, 61 and growth medium, supplemented with recombinant proteins found in cancer cell-conditioned medium, 62 verifying that cancer cells secrete molecules promoting MSC migration. The key molecules inducing MSC migration toward tumors supposedly are vascular endothelial growth factor, 63 fibroblast growth factor 2, 64 stromal cell derived factor 1 (SDF-1), 65 chemokine (C-C motif) ligand 2, also known as monocyte chemotactic protein-1, 66 and macrophage migration inhibitory factor.…”
supporting
confidence: 85%
“…We successfully simulated directional migration of MSCs toward human breast cancer cells and their conditioned medium in vitro. Our results complement the evidence that MSCs tend to migrate toward cancer cells, 13,18 cancer cell-conditioned medium, 61 and growth medium, supplemented with recombinant proteins found in cancer cell-conditioned medium, 62 verifying that cancer cells secrete molecules promoting MSC migration. The key molecules inducing MSC migration toward tumors supposedly are vascular endothelial growth factor, 63 fibroblast growth factor 2, 64 stromal cell derived factor 1 (SDF-1), 65 chemokine (C-C motif) ligand 2, also known as monocyte chemotactic protein-1, 66 and macrophage migration inhibitory factor.…”
supporting
confidence: 85%
“…TGF-β1 is involved in MSC differentiation to CAFs which indeed develop VM. Besides, MSC showed tropism with M2 macrophages, that have been related to tumor aggressiveness [81]. …”
Section: Vasculogenic Mimicry and Tumor Microenvironmentmentioning
confidence: 99%
“…Recently, multiple independent studies have also implicated bone marrow-derived cells, most likely mesenchymal stem cells, as a considerable source of CAFs 413 . Quante et al 10 showed that bone marrow-derived mesenchymal stem cells are actively recruited to the dysplastic stomach, comprising at least 20–25% of αSMA(+) CAFs in a mouse model of inflammation-dependent gastric dysplasia.…”
Section: Introductionmentioning
confidence: 99%